The butcher's boy eaudiobook - Perry, Thomas (Tantor Media, 2008)
Murder has always been easy for the Butcher's Boy—it's what he does best and what they pay him for. But after the successful assassination of a senator, he arrives in Las Vegas to collect his fee only to discover he has become a liability to his shadowy employers. His survival at stake, he needs to kill them before they kill him. But first he needs to find out who they are. As the Butcher's Boy goes to work, police specialists watching the world of organized crime realize something has gone very wrong for the mafia. In the race to discover just what that something is, Elizabeth Waring, a bright young analyst in the Justice Department, is the best chance they have. But is she good enough to catch the Butcher's Boy?